A New Direct Iron Process 1n Relation to Ore and Steel Production - Horace Freeman (Canadian Institute of Mining, Metallurgy and Petroleum, 1959)
"IN THE writer's opinion, the most important industrial re-search problems in Canada concern development of technology for the treatment and commercial utilization of the recent discoveries of v.ast quantities of easily concentrated iron ores in both eastern and western Canada. They exist in both magnetite and hematite forms. The subject is doubly important because of the lack of metallurgical coking coal in Canada. Methods for utilizing our lower grade eastern and western coals for reduction purposes must be developed. We are fortunate in our supplies of oil and gas, which can supply the heat requirements for processing or for thermal electric plants, which are now competitive with hydro-electric plants in the industrial areas. These are among the reasons which have prompted the writer to continue the development of the co-current rotary kiln direct-reduction process outlined •in his report to this Institute at the 1956 Annual Meeting ( 1) in the face of the scepticism which has surrounded the numerous costly failures in 'sponge' or 'direct' iron production. The work involved in bringing the concentrating ores of Canada to the metallic state involves, firstly, concentration of the ores; secondly, preparing the concentrates for reduction; thirdly, reduction of the 'reconstructed' ore; and finally the steel making process. These briefly will be dealt with in order, giving emphasis to the most important of these steps, the reduction process which is the main subject of this paper."